Influence of job satisfaction on organisational citizenship behaviour with moderating role of emotional and career commitments among Indian nurses. (24th January 2023) - Mishra, Amar Kumar; Rai, Anjali; Gujrati, Priyanka; Tiwari, Bhupendra Bahadur
Medical needs of society have become more sophisticated, diversified, and complicated. This has necessitated emphasis on the organisational citizenship behaviour of nurses. The purpose of this study is to empirically examine the direct and indirect effects of job satisfaction, emotional commitment and career commitment on the citizenship behaviour of nurses in organisations. The study has taken job satisfaction as the independent variable, while emotional commitment and career commitment as the moderating variables. The results indicate that job satisfaction has positive and significant direct effect on the organisational citizenship behaviour of nurses. It also indicates the moderating effect of emotional commitment and career commitment in the relationship between job satisfaction and organisational citizenship behaviour. Findings suggest that while JS alone can significantly affect OCB; the presence of EC and CC act as catalyst and strengthens the relation between JS and OCB.